Asuhan Keperawatan Pada An. H Dengan Malnutrisi (Marasmus) Di Bangsal Anggrek III Rumah Sakit Umum Daerah Surakarta - RAMADHAN, RIARDI WAHYU, Siti Arifah, S.Kep., M.Kes (2015)
Bagkground: Complications that may occur in marasmus that decrease the immune system, depression, decreased muscle strength , including respiratory muscle strength, and decreased cardiac function, in patients with marasmus experience muscle wasting, loss of subcutaneous fat, weight loss, slow brain development. Aim of Research: The authors determine the application of nursing care at An.H with Malnutrition kind marasmus. Special Purpose: The writer knows and is able to malakukan assessment, diagnosis uphold, preparing intervention , implement and evaluate the An.H with marasmus at Orchid Lounge Hospital Surakarta. Concluction: nursing actions are performed on patients with the administration of appropriate diet to meet the patient's nutritional program, give appropriate antibiotic therapy and infection control programs to monitor the weight of the patient to determine the patient's growth . Keyword: Marasmus, Nutritional Imbalance, High Risk of Infection.